2017
DOI: 10.1159/000452354
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment Strategy of Achalasia Subtypes and Esophagogastric Junction Outflow Obstruction Based on High-Resolution Manometry

Abstract: Background: Based on Chicago Classification version 3.0, the disorders of esophagogastric junction outflow obstruction (EGJOO) include achalasia (types I, II and III) and EGJOO. Although no curative treatments are currently available for the treatment of the disorders of EGJOO, medical treatments, endoscopic pneumatic dilation (PD), laparoscopic Heller myotomy (LHM), and per-oral endoscopic myotomy (POEM) are usually the sought-after modes of treatment. Since the etiology and pathogenesis might vary depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
(32 reference statements)
1
24
0
3
Order By: Relevance
“…Although the CC v3.0 has helped clarify several issues, especially the varied phenotypes of achalasia, it has also led to the realization that there are circumstances beyond type I, II, and III achalasia in which therapies once reserved for achalasia seem appropriate. In these domains, theories regarding the optimal treatment for each entity are many but evidence remains thin [68][69][70] . Nonetheless, one needs to act on the best evidence available.…”
Section: Poemmentioning
confidence: 99%
“…Although the CC v3.0 has helped clarify several issues, especially the varied phenotypes of achalasia, it has also led to the realization that there are circumstances beyond type I, II, and III achalasia in which therapies once reserved for achalasia seem appropriate. In these domains, theories regarding the optimal treatment for each entity are many but evidence remains thin [68][69][70] . Nonetheless, one needs to act on the best evidence available.…”
Section: Poemmentioning
confidence: 99%
“…Both achalasia and EGJOO are disorders of EGJ outflow obstruction [21, 27] and EGJOO is considered to be a variant of achalasia [19]. Although there was a case report that showed that EGJOO transformed into type II achalasia, it remains unclear whether EGJOO is an early stage of achalasia or a separate disorder.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of the HRM, the Chicago Classification of esophageal motility disorders was proposed to standardize diagnosis of esophageal dysmotility [10], and diagnostic capability has developed dramatically. Disease pathology is increasingly being determined from the view of esophageal motility, and there are now a number of reports of esophageal motility related to clinical symptoms, proton pump inhibitor-resistant non-erosive reflux disease, and achalasia [11-13]. …”
Section: Introductionmentioning
confidence: 99%